A exergia e a sustentabilidade aplicadas a uma usina siderúrgica integrada a carvão vegetal - Lis Nunes Soares (2011)
The exergy concept is the core of this theses, as we herein suggest a link between the ideas of energy, sustainability and the environment. The concept was first used in the analysis of exergy efficiency in conjunction with the energy efficiency analysis of a large integrated charcoal steel plant. For that, data were collected on an annual basis enabling mass, energy and exergy balances of industrial processes present in the mining units, charcoal and integrated steelworks. A highlight was the mass flow of carbon, which resulted in the creation of the baseline on the future possibilities of development of Clean Development Mechanisms (CDM). The analysis identified and quantified the specific consumption and the irreversibility of the processes listed, and with the help of the referenced literature, we detected potential for improving plant efficiency and a situation in terms of energy use of this facility compared to others of the same field. After the overall analysis, the monitoring of a tube production line was done along with its exergoeconomic analysis. This analysis identified and quantified the contribution of each fuel and its exergy inputs in the cost of the tube. Aligned with the global search for sustainable parameters, we suggested the creation of an index of sustainability through a reconstruction of values of products and byproducts which are now parameterized according to an ideal of sustainability. Preliminarily, the data point to an exergetic efficiency of around 43% in the plant studied, excluding the units of charcoal production and mining. Considering these two units, we obtained an exergetic efficiency of around 5% this high difference in levels of efficiency does not justify a comparison between the two conditions, for we took into account the influence of the work of nature (photosynthesis) in the second case. Considering the units of steel production, mining and the carbonization plant, the exergetic efficiency is around 38%. This research suggests that the studied plant, considering the larger context of Brazilian steel industry, and taking sustainability as a parameter for evaluating the quality of consumed energy, follows a differentiated pattern by consuming charcoal as an alternative to coke. The sustainability index proposed indicates that the valuation of products and byproducts of the plant in exergy perspectives, could yield an increase of about 8% in annual revenue. Finally, the potential for increasing the exergy efficiency is the average of other plants with an average improvement index of about 2 GJ per ton of crude steel. This improvement depends on specific actions focused on exergy efficiency, investments in technology as well as research and development